2014
DOI: 10.3846/16111699.2013.859172
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences Affecting Decision-Making Style: A Comparative Study Between Four Countries

Abstract: Abstract. The aim of this paper was to identify the impact of national culture on decision-making styles in selected countries: Croatia, Slovenia, Bosnia and Herzegovina and Hungary. The estimation of Hofstede's dimensions of national cultures and comparative analyses was carried out by using a narrow-sample strategy. The estimated positions on each dimension confirmed the Hofstede's original research ranking. The result with significant value was the confirmation of the global trend of decreasing power distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Podrug et al (2006) used VSM94 for cross-cultural comparison between three Central European countries, Croatia, BiH and Slovenia; and Tipurić, Podrug, and Hruška (2007) used the same module to examine the cultural differences in Croatia, Slovenia, BiH and Hungary. In their most recent research, Dabić, Tipurić, and Podrug (2015) compared Croatia, Slovenia, BiH and Hungary, and Podrug, Filipović, and Stančić (2014) conducted comparative research for Croatia, Brazil, Germany, Serbia and Spain, both using the VSM 94 instrument. All previous empirical studies support the argument that it is preferable to use the VSM 94 in calculating national culture indices for Croatia, following the procedures described below.…”
Section: Methodsmentioning
confidence: 99%
“…Podrug et al (2006) used VSM94 for cross-cultural comparison between three Central European countries, Croatia, BiH and Slovenia; and Tipurić, Podrug, and Hruška (2007) used the same module to examine the cultural differences in Croatia, Slovenia, BiH and Hungary. In their most recent research, Dabić, Tipurić, and Podrug (2015) compared Croatia, Slovenia, BiH and Hungary, and Podrug, Filipović, and Stančić (2014) conducted comparative research for Croatia, Brazil, Germany, Serbia and Spain, both using the VSM 94 instrument. All previous empirical studies support the argument that it is preferable to use the VSM 94 in calculating national culture indices for Croatia, following the procedures described below.…”
Section: Methodsmentioning
confidence: 99%
“…Geert Hofstede being considered a key figure in work-related cultural studies (Dupuis, J., 2014), triggered numerous further studies in the field, based on his ideas. According to his findings, people within an organization behave and react to certain situations in accordance with their "collective programming" meaning the culture (Dabic et al,2015). As the result of his cultural research Hofstede has identified six key work-related cultural dimensions: Uncertainity avoidance; Power Distance; Indivisualism/Collectivism; Masculanity/ Femininity; Longterm Orientation; and Indulgence/Restraint.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, what inpatriate managers expect from their HQ environment, and what they do to influence it, will undoubtedly be swayed by their preexisting beliefs and attitudes (Kelley & Michela, ; McArthur, ), which are argued to be strongly influenced by their cultural background (Tung & Verbeke, ). Cultural value differences between managers from HQ and managers from subsidiaries have shown repeatedly that there is little evidence of convergence (Dabić, Tipurić, & Podrug, ; Mellahi & Collings, ). The second antecedent is their motivation.…”
Section: Attributions In the Context Of The Inpatriate Managermentioning
confidence: 99%